Meningkatkan Kreativitas Belajar pada Pembelajaran PAKBP dengan Model PBL Fase C Kelas V Sekolah Dasar Negeri 11 Paat Kecamatan Embaloh Hulu - Petronila Merlin (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to increase the learning creativity of class V students in the subject of Catholic Religious Education and Character (PAKBP) through the application of the Phase C Problem Based Learning (PBL) model. PBL was chosen because it encourages students to be more active in solving real problems, thinking critically, and develop creativity. This classroom action research was carried out at the Paat 11 State Elementary School, Embaloh Hulu District, with a focus on the material "The Holy Spirit Strengthens the Hearts of the Apostles". The research results show that the application of the Phase C PBL model can increase students' creativity in understanding and applying the values ​​of Catholic teachings in everyday life. Apart from that, this method also succeeded in increasing learning motivation and student involvement in learning. Thus, PBL Phase C is effective in improving the quality of PAKBP learning and can be used as an alternative learning model to enrich student creativity.